All non-indigenous species were introduced recently? The case study of Cassiopea (Cnidaria: Scyphozoa) in Brazilian waters - Morandini, Andre C.; Stampar, Sergio N. [UNESP]; Maronna, Maximiliano M.; Da Silveira, Fabio L. (Cambridge Univ Press, 2017)
Upside-down jellyfish (genus Cassiopea) can be found in tropical coastal waters worldwide. Until now reports of the genus from Brazilian waters have been scant. We report here medusae and scyphistomae collected from Cabo Frio, Rio de Janeiro state. Although we could not unambiguously identify the material using morphological criteria, genetic sequence data (COI) indicate that the Brazilian jellyfishes are genetically similar to those from Bermuda, Hawaii and Florida, which are related to specimens from the Red Sea (Cassiopea andromeda). We hypothesize that the presence of C. andromeda in Brazil is due to an invasion event, as the scyphistomae were found growing over the known invasive ascidian Styela plicata. Estimation of divergence time between Brazil (Cabo Frio) and Florida/Bermuda populations is that it occurred at the beginning of ship movement to South America.
Keywords: Invasive species; marine; rhizostome; jellyfish; blooms